The relationship between cadmium and cognition in the elderly: a systematic review - Xueke Yang; Lijing Xi; Zhaoyan Guo; Li Liu; Zhiguang Ping (Taylor & Francis Group, 2023)
Context: The relationship between cadmium (Cd) and the cognition of the elderly is indistinct. Objective: To summarise the studies on the relationship between the cognition of the elderly and Cd. Methods: Literatures were searched in PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Wan fang database on April 25, 2022. The entries in the STROBE statement were used to evaluate the literature quality; all the quantitative studies that met the requirements were systematically summarised. Results: Blood Cd was negatively correlated with the cognitive ability of the elderly, corresponding to different cognitive ability assessment methods, the regression coefficients were: −0.11 (−0.20, −0.03), −0.46 (−0.71, −0.21), −0.54 (−0.90, −0.17), −0.19 (−0.37, −0.01), and −2.29 (−3.41, −1.16). The regression coefficients between urinary Cd level and cognition score were −1.42 (−2.38, −0.46), and 0.76 (−1.28, −0.23). When dietary Cd increased by 1 μg/kg, the composite z-score decreased by 3.64 (p = 0.001). There was no significant correlation between drinking water Cd, fingernail Cd and cognition (p > 0.05). Conclusion: We concluded that blood Cd (including whole blood and plasma), urine Cd and dietary Cd were negatively correlated with the cognition of the elderly, but the relationship between Cd in drinking water and fingernails and cognition was not statistically significant.